Pengaruh Core Stability Terhadap Penurunan Nyeri Punggung Bawah Pada Penderita LBP Myogenic di RSUD dr. R . Soedarsono Kota Pasuruan - Arifiyanto, Ahmad Syarwani; Halimah, Nurul; Wardoyo, Puspo; Pradita, Angria (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
Objective: Low Back Pain is a problem such as chronic or acute pain in the lower back or in the lumbar region. This pain can be caused by inflammation or degeneration or due to aging or increasing age and can also be due to trauma.Methods: This research is an experimental study using a one group pretest post test design approach which was conducted in October 2021. The independent variable in this study is core stability, and the dependent variable is the pain level of sufferers of Low Back Pain. The population of this study was 30 patients. The methods that will be used for core stability are plank, bridging, and Prone Back Extension. The number of samples in this study were 30 respondents, using purposive sampling technique with inclusion criteria of LBP patients aged 30-50 years, feeling pain in the lower back, patients who were willing and cooperative to become objects until the study was completed, had blood pressure with diastolic 70-90 MmHg and systole 110-150 mmHg. While the exclusion criteria for LBP sufferers are in a period of special treatment (bed rest), have physical disabilities (disability), have had surgery in the back area, the patient is taking medication, the patient refuses to be a respondent. Research data collection was carried out for 4 weeks doing physiotherapy 2 times a week. Measurement of pain level using the Visual Analogue Scale. Collecting data in this study using primary data. The researcher asked the respondent's characteristics including gender, age, and the results of the observation on the level of pain to the respondent.Results: The significance value of the Wilcoxon Ranks test is 0.000 <α (α = 0.05), then there is an effect of Core stability on reducing low back pain in patients with Myogenic LBP at RSUD dr. R. Soedarsono Pasuruan City.Conclusion: 1)The average value of low back pain before administering Core stability to patients with Myogenic LBP is 5.20, which is included in the moderate pain level. 2)The average value of low back pain after administering Core stability to patients with Myogenic LBP is 3.83, which is included in the level of mild pain. 3) There is an effect of Core stability on the reduction of low back pain in patients with Myogenic LBP in RSUD dr. R. Soedarsono Pasuruan City with p-value = 0.000 (p<0.05)